PELESAPAN DAN PERUBAHAN FONEM PADA BAHASA ANAK USIA BALITA DI KECAMATAN BONTOMANAI GOWA - Nursamsilis Lutfin (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2021)
This study aims to absorb and change phonemes in the language of toddlers in the Bontomanai sub-district, Gowa Regency. Researchers used a qualitative descriptive research design. In this study, the researcher used the observation method. Observation or direct observation of the research object was intended to get a clear picture of the existence of the research object and the activities carried out. Through this method, researchers can see directly the activities carried out by children in communicating with the people around them. The data in this study were collected by observation method with recording and note taking techniques. Data analysis activities in this study include data identification, data presentation and drawing conclusions. In identifying the data, the researcher gives the code to the appropriate data. The next stage is the presentation of data. The data presented in the form of phonetics, morphemes, and sentences will then be analyzed after drawing conclusions. Based on the results of the discussion described in chapter IV, it can be concluded that 1) Research activities on the language of children aged 2-5 years in the Bontomanai District experienced deletion in almost all phonemes, both vowels and consonants. Phoneme /l/, phoneme /a/ at the beginning of a word and /k//k/ phoneme /b/ at the beginning of a word, /j/ at the beginning of a word, /l/ in the middle of a word, several phonemes are dropped at once namely /m/, /e/ and /b/, omission of phonemes /j/, omission of phonemes /s/, omission of phonemes /r/, omission of phonemes /k/, omission of phonemes /d/, and omission of phonemes /f/. 2) Research activities on the language of children aged 2-5 years in the Bontomanai District experience phoneme changes. phoneme /r/ changes to /y/, phoneme changes from /g/ to /n/, phoneme changes from /r/ to /y/, phoneme /r/ changes to /l/, changes occur to phoneme /s / becomes /c/, changes from phoneme /r/ to phoneme /l/, changes from phoneme /r/ to phoneme /b/, changes from phoneme /f/ to phoneme /p/, changes to phoneme /r/ to /l/, changes to the phoneme /f/ becomes /p/. 3) The impact of deletion and phoneme changes that occur in children in Bontomanai Gowa District. The word for take becomes ambi, the word for Fajar becomes ajar, and the word effect becomes epek